FMNL1 Exhibits Pro-Metastatic Activity via CXCR2 in Clear Cell Renal Cell Carcinoma - Zhang, Mei-Fang; Li, Qiu-Li; Yang, Yu-Feng; Cao, Yun; Zhang, Chris Zhiyi (Frontiers in Oncology, 2020)
Formin-like (FMNL) proteins are responsible for cytoskeletal remodeling and have been implicated in the progression and spread of human cancers. Yet the clinical significance and biological function of FMNL1 in clear cell renal cell carcinoma (ccRCC) remain unclear. In this study, the expression of FMNL1 in ccRCC and its clinical value were determined by tissue microarray-based IHC and statistical analyses. The role of FMNL1 in ccRCC metastasis and the underlying mechanism were investigated via in vitro and in vivo models, using gene regulation detection, ChIP, Luciferase reporter assays and rescue experiments. We show that FMNL1 is upregulated in ccRCC and exhibits pro-metastatic activity via induction of CXCR2. High expression of FMNL1 is significantly correlated with advanced tumor stage, higher pathological tumor grade, tumor metastasis and unfavorable prognosis in two independent cohorts containing over 800 patients with ccRCC. The upregulation of FMNL1 in ccRCC is mediated by the loss of GATA3. Ectopic expression of FMNL1 promotes, whereas FMNL1 depletion inhibits cell migration in vitro and tumor metastasis in vivo. The FMNL1-enhanced cell mobility is markedly attenuated by the knockdown of CXCR2. Further studies demonstrate that FMNL1 increases the expression of CXCR2 via HDAC1. In clinical samples, FMNL1 expression is positively associated with CXCR2, and is negatively connected to GATA3 expression. Collectively, our data suggest FMNL1 serve as a potential prognostic factor and function as an oncogene. The axis of GATA3/FMNL1/CXCR2 may present a promising therapeutic target for tumor metastasis in ccRCC.